Riesz basis property of Timoshenko beams with boundary feedback control - De-Xing Feng; Gen-Qi Xu; Siu-Pang Yung (International Journal of Mathematics and Mathematical Sciences)
A Timoshenko beam equation with boundary feedback control is considered. By an abstract result on the Riesz basis generation for the discrete operators in the Hilbert spaces, we show that the closed-loop system is a Riesz system, that is, the sequence of generalized eigenvectors of the closed-loop system forms a Riesz basis in the state Hilbert space.